Management of chronic kidney disease- an update - Ahammad, Faruk (Faridpur Medical College Journal, 2015)
Chronic kidney disease (CKD) is a global public health issue demanding continuous improvement in its management. Different international groups and organizations have now achieved a good progress in its definition, classification (staging), treatment and referral criteria to nephrologists. In definition of CKD, "CKD is defined as abnormalities of kidney structure or function, present for at least three months with implications for health", the phrase "with implications for health" has been added at the end of the previous definition, which reflects the concept that there may be certain abnormalities of kidney structure or function that do not have prognostic consequences (for example, a simple renal cyst). At staging of CKD, grade 3 has been subdivided into G3a and G3b, according to whether the glomerular filtration rate (GFR) is (59 - 45) or (44 - 30) ml/min/1.73m2, respectively. Furthermore, albuminuria has been classified in any GFR grade, in to A1, A2 or A3 according to the albumin-creatinine ratio (ACR) in an isolated urine sample for values <3, 3-30 or >30mg/mmol, respectively. The term "microalbuminuria" has now been replaced by the term "moderately increased albuminuria". For GFR measurement Chronic Kidney Disease Epidemiology Collaboration (CKD- EPI) equation has been preferred than the Modification of Diet in Renal Disease (MDRD) study equation and new 2012 KDIGO guidelines consider the use of alternative formulas to be acceptable if they have been shown to improve accuracy when compared with the CKD-EPI formula. For detection of albuminuria ACR is preferred rather than conventional 24 hours urine albumin. The recommended BP control target is ?140/90mmHg (both diabetic and non-diabetic) if ACR <3mg/mmol and a stricter target is suggested, with BP ?130/80mmHg, (both in diabetic and non-diabetic) if the ACR is ? 3mg/mmol. Use of erythropoisis-stimulating agent (ESA) in anemia of CKD should be rational; to avoid its adverse effects like stroke, thrombosis or hypertension acceleration and hemoglobin goals should not exceed 11 g per dl. Treating dyslipidaemia in CKD with statins for all adults >50 years of age, irrespective of low density lipoprotien (LDL) cholesterol levels is recommended. Referral to nephrologist should be rational according to guidelines and at least one year prior to the start of renal replacement therapy (RRT). Faridpur Med. Coll. J. 2014;9(1): 46-52